LITERATURE AS MEDIA FOR DEVELOPING LANGUAGE COMPETENCE AND BUILDING SOCIAL AWARENESS - Mu’in, Fatchul (English Department of Faculty of Tarbiyah and Teachers Training, 2013)
Literature is a kind of the artwork which uses a language as a medium. If it said that literature is a language in one side, learning literature is, at the same time, learning a language in the other side. English literature is literature written in English language. In this relation, learning English literature is, at the same time, learning English language. If literature talks about human life, by using literary works we can learn and build our social awareness, and at almost the same time we can contribute to nation character building. In this paper, the writer offers the mechanism of how the literary works can be used to develop language competence (in listening, speaking, reading and writing) and the advantages of learning the literary works in relation to the social awareness building or nation character building.